Preretirees Retirement Planning as Precondition of Their Future Wellbeing: Review of Foreign Studies - T.V. Drobysheva; I.V. Larionov; S.V. Tarasov; A.N. Knigolyubova (Современная зарубежная психология, 2025)
The article represents a review of foreign studies devoted to the process of retirement planning among pre-retirees and its correlation with retirement well-being. Theoretical approaches in the study of retirement process are analyzed: processual (level), systemic (in some works — staged) and resource approach. It is shown that the advantage of systemic (staged) approach is that it analyzes not only multilevel organization of factor’s system of pre-retirees’ readiness for planning, but also interdependence of factors in the system. The prospects of the procedural approach are related to the identification of mechanisms for the transition from one planning stage to another. The development of the resource approach involves studying the ability of pre-retirees to plan their retirement as a cognitive resource, which contributes to the success of transition from work to retirement. As a result of analysis the spheres of retirement planning are highlighted. The ability to plan in financial, social, leisure and health spheres is considered as precondition for the psychological well-being of a pre-pensioner after retirement. Planning performs the function of readiness to change social roles, financial position and helps a person to adapt to changes in lifestyle while maintaining subjectively significant social activity.